Psicogênese, autoctisi e escola viva: conceitos assertivos de Clemente Quaglio - Monarcha, Carlos Roberto da Silva [UNESP] (My University, 2011)
This essay, linked to the project “Clemente Quaglio (1872-1948): pedological canon of science - historical critical study, denotes aspects from Clemente Quaglio’s scientific production. Consultations with institutional archives enabled to summon documentary sources of lower historiographical status - educational and scientific pamphlets - and interpret them with appropriate theoretical framework. This research aims to prioritize the study of theconcepts of psychogenesis, autoctisi and living school, contained in the re-elaboration of the pedologist’s theroretical plan.

Esta comunicação, vinculada ao projeto “Clemente Quaglio (1872-1948): cânon da ciência pedológica — estudo histórico-crítico, demarca aspectos da produção científica de Clemente Quaglio. Consultas a acervos institucionais possibilitaram convocar fontes documentárias de menor estatuto historiográfico — opúsculos didático-científicos — e interpretá-las com referencial teórico apropriado. Os objetivos da pesquisa priorizaram o estudo dos conceitos de psicogênese, autoctisi e escola viva, constantes na reelaboração do plano teórico do pedologista.
Psychogenesis, autoctisi and living school: Clemente Quaglio’s assertive concepts
Keywords: Clemente Quaglio; Psychogenesis; Autoctisi; Clemente Quaglio; Psicogênese; Autoctisi